Target Deformation of the Equus stenonis Holotype Skull: A Virtual Reconstruction - Cirilli, Omar; Melchionna, Marina; Serio, Carmela; Bernor, Raymond L.; Bukhsianidze, Maia; Lordkipanidze, David; Rook, Lorenzo; Profico, Antonio; Raia, Pasquale (Frontiers in Earth Science, 2020)
Equus stenonis is one of the most prevalent European Pleistocene fossil horses. It is believed to be the possible ancestor of all Old World Early Pleistocene Equus, extant zebras and asses, and as such provides insights into Equus evolution and its biogeography and paleoecology. The Equus stenonis holotype skull (IGF560) was first described by Igino Cocchi in 1867, from the Early Pleistocene locality of Terranuova (Upper Valdarno basin, Italy). IGF560 is a nearly complete, although medio-laterally crushed and badly compressed skull. Here we provide the first application of a new virtual reconstruction protocol, termed Target Deformation, to the Equus stenonis holotype. The protocol extends beyond classic retrodeformation by using target specimens as a guide for the virtual reconstruction. The targets used as a reference are two fragmentary, yet well-preserved E. stenonis skulls, coming from Olivola (Italy; IGF11023) and Dmanisi (Georgia; Dm 5/154.3/4.A4.5), both Early Pleistocene in age. These two specimens do not display any major deformation, but preserve different, only slightly overlapping portions of the skull. The virtual reconstruction protocol we carried out has shown its feasibility, by producing two 3D models whose final morphology is perfectly congruent with the natural variability of a comparative sample of E. stenonis specimens. This study shows the potential of using even broken or otherwise fragmentary specimens to guide retrodeformation in badly distorted and damaged specimens. The application of Target Deformation will allow us to increase the availability of comparative specimens in studies of fossil species morphology and evolution, as well as to the study of taphonomic processes.